HUBUNGAN KETERPAPARAN IKLAN, AKSES DAN PERATURAN PERUNDANG-UNDANGAN DENGAN PERILAKU MEROKOK PETUGAS RUMAH SAKIT HM RYACUDU KOTABUMI KABUPATEN LAMPUNG UTARA - Deni Metri; Bambang Murwanto (Jurnal Kesehatan Metro Sai Wawai, 2016)
Smoking behavior can happen cause of advertisement exposure, access to get cigarette and legislation. Moreover as a provider of health service as a no smoking area that shiud be role models for society. Seventy percent of mayjen ryacudu hospital employees are smoking. Researcher want to know how correlation of advertisement exposure, access, and legislation so smoking behavior in ryacudu hospital kotabumi. This study design is analytic quantitative use cross sectional approach and quantitative to complete quantitative study and doing indepth interview with 5 people of management of hospital that are: director, head of administration, head of nursing, head of medical service, and head of PKRS. Population of this study are all of employee of ryacudu hospital kotabume that have total 611 employees. Sample of this study are 97 employees with proportio random sampling technique. Data analysis use chi square test with α=0,05. The result of this study get smoking employees are 41,3%, advertisement exposure is 52,6, easy access to get cigarette is 84,5%, legislation is 34%. No coreelation between advertisement exposure and smoking behavior )p value = 0,527) and no correlation between easy access and smoking behavior (p value=0,336). There is correlation between legislation and smoking behavior )p value = 0,000) observation result is find there is board ban of vend in hospital area and there is no regent legislation about no smoking area in hospital. Interview with hospital director say if legislation is not yet socialized.